Effects of skim milk powder enriched with glycomacropeptide and G600 milk fat extract on frequency of gout flares: a proof-of-concept randomised controlled trial. Issue 6 (23rd January 2012) - Dalbeth, Nicola; Ames, Ruth; Gamble, Greg D; Horne, Anne; Wong, Sumwai; Kuhn-Sherlock, Barbara; MacGibbon, Alastair; McQueen, Fiona M; Reid, Ian R; Palmano, Kate
Abstract : Objectives: Previous laboratory studies have identified two dairy fractions, glycomacropeptide (GMP) and G600 milk fat extract (G600), with anti-inflammatory effects in models of acute gout. The aim of this proof-of-concept clinical trial was to test the hypothesis that daily intake of skim milk powder (SMP) enriched with GMP and G600 can prevent gout flares. Methods: This was a 3-month randomised double-blind controlled trial of milk products for prevention of gout flares. One hundred and twenty patients with recurrent gout flares were randomised to one of three arms: lactose powder control, SMP control and SMP enriched with GMP and G600 (SMP/GMP/G600). The primary end point was change in the frequency of gout flares using a daily flare diary measured monthly for 3 months. Results: The frequency of gout flares reduced in all three groups over the 3-month study period compared with baseline. Over the 3-month study period there was a significantly greater reduction in gout flares in the SMP/GMP/G600 group (analysis of covariance pgroup =0.031, Tukey post hoc test compared with lactose control, p=0.044). Following treatment with SMP/GMP/G600 over the 3-month period, greater improvements were also observed in pain and fractional excretion of uric acid, with trends to greater improvement in tender joint count. Similar adverse event rates and discontinuation rates were observed between the three groups. Conclusions: This is the first reported controlled trial of dietary intervention in patients with gout, and suggests that SMP enriched with GMP and G600 may reduce the frequency of gout flares.